Identifikasi Golongan Darah ABO dengan Metode Absorpsi Elusi pada Sampel Bercak Darah dari Lingkungan yang Berbeda - Sari, Indah (Indonesian Journal of Legal and Forensic Sciences (IJLFS); Vol 14 No 2 (2024): Indonesian Journal of Legal and Forensic SciencesDO - 10.24843/IJLFS.2024.v14.i02.p06, 2025)
Background: identification of ABO blood group is easier with fresh blood samples than with dry blood samples. A commonly used method for determining blood type in dry blood samples is the absorption elution method. This method is very sensitive and can indirectly detect the presence of antigens. Purpose: this study aims to study changes in ABO blood group in dry blood sample from different environments using absorption elution method. Methods: this study used a static group comparison design with 16 dry blood spot samples collected from subjects with a known blood type and stored for 8 weeks under two different conditions indoors and outdoors. Blood samples were then tested for ABO blood group by absorption elution method, and the resulting data were processed using descriptive analysis. Results: testing samples taken from the room showed the results of 56.25% change and 43.75% did not change the blood group. Examination of samples from outside the room showed 12.50% had changes and 87.50% had no changes in blood type. Conclusion: it can be concluded that there was a change in blood group in the dry blood spot sample due to environmental influences, and there were fewer changes in blood group in the indoor sample than in the outdoor sample.